Desempenho ao ruído de impacto de laje pré-fabricada nervurada de vigotas protendidas e tavelas cerâmicas com revestimento de pisos vinílicos - Rossi, Camila Taciane (2020)
With the growth of demand for dwellings in the urbane centers, the civil construction has been suffering with the lack of resources bringing in the reduction of costs and rationalization of processes and products, thus generating the reduction of slab and wall thicknesses, causing the loss of performance of the new buildings, which contributes to the emergence of problems related to impact noise from walking people and animals, falling objects, among other. In view of that, the Brazilian Association of Technical Standards (ABNT) prepared the NBR 15.575 in 2013 named as: housing buildings – performance, which points out the minimum requirements that must be adopted by new constructions, to ensure the quality of life of users. Therefore, this study sought to know the acoustic performance of impact noise in prefabricated ribbed slabs with prestressed joists with the use of vinyl flooring as a coating, as well as to test the use of floating floors with several resilient materials. The tests were performed at the UFSM thermal acoustics laboratory, in accordance with the criteria defined by ISO 16283-3:2018 e a ISO 717- 2:2013, to determine the weighted standard impact sound pressure level (L’nT,w) of each composition tested, and thus, be able to verify that the solutions meet the menimum values required by NBR 15575- 3:2013. It can be conclued that of the 13 specimen of vinyl flooring studied, in the slab + counterfloor (4cm) + vinyl flooring, only one did not complied with minimum requirements with 82 dB, eleven specimens are rated at the minimum level, varying from 67 dB to 80 dB and one at the intermediate level with 64 dB. From that, 6 specimens were selected, with the best, intermediate and worse results, to the realization of tests the floating floor system solution, qith nine resiliente materials. The vast majority of the compositions are intermediate level varying between 62 to 56 dB, with 23 specimens in the upper level ≤ 55. Therefore, all the tested floating floor systems can be implemented together to the constructive system of this slab, classifying within the parameters required by the Brazilian performance standard for flooring systems separating autonomous housing units. Regarding the floor system requirement separating áreas of collective use over autonomous units, 15 specimens fall into the minimum level, 5 into the intermediate level and 3 specimens into the upper level. The information obtained in this research, is intended to serve as a cupport for recommendations and interventions in civil construction, improving the quality of life of users of multiple floor buildings.